2018
DOI: 10.1038/s41598-018-35122-y
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length and risk of coronary heart disease and stroke mortality: prospective evidence from a Russian cohort

Abstract: Previous studies suggest that reduced leukocyte telomere length (LTL) is related to higher risk of mortality and several chronic conditions, including coronary heart disease (CHD) and stroke. However, the consistency of this association differs across populations. We investigated the relationship of LTL with CHD, stroke and all-cause mortality together with non-fatal CHD and stroke events in a Russian cohort with a mean age of 58 years at baseline. Data from 1,144 individuals in the Russian subset of the Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In our study, an epigenetic predictor of telomere length predicted time-to-onset of ischemic heart disease. A shorter leukocyte telomere length has been shown to associate with heart disease in diverse populations, suggesting that the DNAm Telomere Length predictor may capture key facets of this clinical association [42][43][44]. Our rich resource of genome-wide DNA methylation and longitudinal health data is the first to show the association of epigenetic measures of ageing with a wide range of common disease states, even after accounting for major confounding influences.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an epigenetic predictor of telomere length predicted time-to-onset of ischemic heart disease. A shorter leukocyte telomere length has been shown to associate with heart disease in diverse populations, suggesting that the DNAm Telomere Length predictor may capture key facets of this clinical association [42][43][44]. Our rich resource of genome-wide DNA methylation and longitudinal health data is the first to show the association of epigenetic measures of ageing with a wide range of common disease states, even after accounting for major confounding influences.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an epigenetic predictor of telomere length predicted time-toonset of ischemic heart disease. A shorter leukocyte telomere length has been shown to associate with heart disease in diverse populations, suggesting that the DNAm Telomere Length predictor may capture key facets of this clinical association (32)(33)(34). Our rich resource of genome-wide DNA methylation and longitudinal health data is the first to show the association of epigenetic clocks with a wide range of common disease states, even after accounting for major confounding influences.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, among a community-based cohort of African Americans, after a median follow-up of 9 years, longer telomere length was associated with a lower risk of incident ischemic stroke and total mortality in age- and sex-adjusted models, but these associations were no longer significant in fully adjusted models [21]. However, there were also a large number of studies that suggested telomere length relating to all-cause mortality in different population [22,23].…”
Section: Discussionmentioning
confidence: 99%